2007
DOI: 10.1016/j.brainresbull.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative developmental neurotoxicity of organophosphates in vivo: Transcriptional responses of pathways for brain cell development, cell signaling, cytotoxicity and neurotransmitter systems

Abstract: Organophosphates affect mammalian brain development through a variety of mechanisms beyond their shared property of cholinesterase inhibition. We used microarrays to characterize similarities and differences in transcriptional responses to chlorpyrifos and diazinon, assessing defined gene groupings for the pathways known to be associated with the mechanisms and/or outcomes of chlorpyrifos-induced developmental neurotoxicity. We exposed neonatal rats to daily doses of chlorpyrifos (1 mg/kg) or diazinon (1 or 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
208
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(224 citation statements)
references
References 112 publications
(222 reference statements)
13
208
0
3
Order By: Relevance
“…The results point to key divergences between chlorpyrifos and diazinon: just as we concluded earlier for the FGF family [79] the two organophosphates elicit differing alterations in neurotrophic factors that may ultimately contribute to disparities in the impact on neural pathways and behavior. Indeed, we already have substantial evidence for differing susceptibilities and damage to cholinergic and serotonergic pathways from neonatal chlorpyrifos exposure as compared to diazinon [75][76][77]81]. In turn, the fact that the two agents diverge in important ways reinforces the fact that the developmental neurotoxicity does not depend solely on the shared property of cholinesterase inhibition but rather reflects critical contributions of other mechanisms such as effects on neurotrophic factors [77,79].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results point to key divergences between chlorpyrifos and diazinon: just as we concluded earlier for the FGF family [79] the two organophosphates elicit differing alterations in neurotrophic factors that may ultimately contribute to disparities in the impact on neural pathways and behavior. Indeed, we already have substantial evidence for differing susceptibilities and damage to cholinergic and serotonergic pathways from neonatal chlorpyrifos exposure as compared to diazinon [75][76][77]81]. In turn, the fact that the two agents diverge in important ways reinforces the fact that the developmental neurotoxicity does not depend solely on the shared property of cholinesterase inhibition but rather reflects critical contributions of other mechanisms such as effects on neurotrophic factors [77,79].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we already have substantial evidence for differing susceptibilities and damage to cholinergic and serotonergic pathways from neonatal chlorpyrifos exposure as compared to diazinon [75][76][77]81]. In turn, the fact that the two agents diverge in important ways reinforces the fact that the developmental neurotoxicity does not depend solely on the shared property of cholinesterase inhibition but rather reflects critical contributions of other mechanisms such as effects on neurotrophic factors [77,79]. Indeed, recent studies reinforce the separation of the effects observed here from those that depend on anticholinesterase effects: chronic, intermittent chlorpyrifos exposures in adults that are nonsymptomatic but well above the threshold for cholinesterase inhibition produce cognitive impairment in association with deficits in ntrk1, a subtype that was unaffected in our studies with lower exposures in the developing rat brain [90].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is now clear that, in addition to cholinergic hyperstimulation consequent to inhibition of cholinesterase activity, OPs like chlorpyrifos (CPF) elicit their adverse effects on brain development through a family of mechanisms including direct effects on neural cell replication and differentiation [20,21]. Thus, although doses of CPF or other OPs high enough to cause substantial cholinesterase inhibition disrupt the pattern of genes that are essential to neurodevelopment [5,6], widespread changes in these genes are evident at much lower exposures that lie below the threshold for cholinesterase inhibition [23,24].…”
Section: Introductionmentioning
confidence: 99%